Research skills and digital competence in Huancavelica students during COVID-19 - Riveros-Anccasi, Daker; Riveros-Terrazo, Lizeth Karina; Cayllahua-Yarasca, Ubaldo; Anccasi-Juan, Charapaqui; Rojas-Quispe, Angel Epifanio; Torres-Acevedo, Christian Luis; Laurente-Chahuayo, Carlos (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study addresses the challenge of developing research skills among teacher training students at the National University of Huancavelica during the COVID-19 pandemic, focusing on the role of digital competencies. Using a quantitative, descriptive correlational design, data were collected from 180 students across four professional education programs in the VII and IX cycles. Two questionnaires, comprising 40 and 45 questions respectively, assessed digital competencies and research skills. The data, analyzed using SPSS (version 25) with a 5% margin of error, revealed a strong positive correlation (Rho=0.808) between digital competencies and research skills. Students with higher digital literacy, particularly in information and data literacy and communication and collaboration, demonstrated better proficiency in research tasks such as designing methodologies, data analysis, and presenting findings. The study emphasizes the importance of integrating digital skills into teacher education to enhance research capabilities, especially in post-pandemic educational contexts. Notably, 60% of students with “excellent” digital competency levels achieved “excellent” research skills, compared to only 10% with “good” competencies. These findings underscore the need to prioritize digital literacy in teacher education programs to support the development of essential research skills.